2004
DOI: 10.1210/en.2003-0853
|View full text |Cite
|
Sign up to set email alerts
|

Brain-Derived Neurotrophic Factor and Androgen Interact in the Maintenance of Dendritic Morphology in a Sexually Dimorphic Rat Spinal Nucleus

Abstract: Testosterone regulates androgen receptor expression, soma size, and dendritic length in motoneurons of the spinal nucleus of the bulbocavernosus (SNB) in adult male rats. Brain-derived neurotrophic factor (BDNF) is also expressed in SNB motoneurons; BDNF maintains SNB soma size in castrates, and interacts with testosterone to regulate androgen receptor expression in SNB motoneurons. This study tested the hypotheses that BDNF promotes SNB dendritic lengths and that BDNF and testosterone interact to maintain den… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
56
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(58 citation statements)
references
References 62 publications
2
56
0
Order By: Relevance
“…In B6D2F1 mice, the length of SNB dendrites did not appear to be dependent on adult levels of androgen. While there is no information to date on the mechanisms underlying the androgenic regulation of dendrites in mice, we can draw again from evidence obtained from rats which suggests that androgens in adulthood act directly on the BC/LA muscles to indirectly regulate the length of SNB dendrites (Rand & Breedlove, 1995) and this androgen action may be mediated via some muscle-derived factor such as brain derived neurotrophic factor (Yang et al, 2004). We report that BC/LA muscle mass in adult C57BL6J mice is highly androgen-dependent, as in rats (Venable, 1966).…”
Section: Discussionmentioning
confidence: 98%
“…In B6D2F1 mice, the length of SNB dendrites did not appear to be dependent on adult levels of androgen. While there is no information to date on the mechanisms underlying the androgenic regulation of dendrites in mice, we can draw again from evidence obtained from rats which suggests that androgens in adulthood act directly on the BC/LA muscles to indirectly regulate the length of SNB dendrites (Rand & Breedlove, 1995) and this androgen action may be mediated via some muscle-derived factor such as brain derived neurotrophic factor (Yang et al, 2004). We report that BC/LA muscle mass in adult C57BL6J mice is highly androgen-dependent, as in rats (Venable, 1966).…”
Section: Discussionmentioning
confidence: 98%
“…The BC/LA muscles produce brain-derived neurotrophic factor (BDNF) (Yang and Arnold, 1999). By applying BDNF peripherally to cut BC/LA nerves, Yang et al (2004) showed that SNB dendritic morphology can be regulated by trophic substances from the neuromuscular periphery as long as testosterone is also present. The requirement for testosterone may be at least partially due to the fact that the expression of the BDNF receptor, trkB, in SNB motoneurons is regulated by T: motoneurons of castrated animals deprived of T show reduced expression of trkB receptors compared to motoneurons of intact animals or castrated animals given T replacement (Osborn et al, 2007;Ottem et al, 2007).…”
Section: Neurotherapeutic Effectsmentioning
confidence: 99%
“…In animal studies, exercise increases production of local growth factors including brain-derived neuotropic factor (BDNF) that may affect brain function (10). Testosterone and BDNF interact to maintain dendritic morphology in the rat spinal nucleus (11). Therefore, it is conceivable that the addition of an exercise program to testosterone administration may have additive effects on mental function and quality of life in elderly men as well.…”
Section: Introductionmentioning
confidence: 99%